PRESCRIÇÃO DA PENA CRIMINAL E INELEGIBILIDADE: TEMAS INEXPLORADOS E FUTUROS OVERRULING’S NA JURISPRUDÊNCIA DO TSE - Espíndola, Ruy Samuel (Revista da AJURIS - Qualis A2, 2017)
THE EXPIRY OF THE STATUTE OF LIMITATIONS ON THE CRIME AND THE UNELECTABLE CONDITION: UNEXPLORED THEMES AND FUTURES OVERRULING’S ON SUPERIOR ELECTORAL FEDERAL COURT OF BRAZIL JURISPRUDENCE RESUMO: Este artigo trata dos efeitos da prescrição da pena criminal sobre o direito fundamental de candidatura e critica precedente Respe 23.851-TSE, que definiu que a partir da prescrição da pena começaria a fluir o tempo de inelegibilidade, reclamando overruling. Demonstra que a ratio decidendi não guarda congruência com o direito positivo, à dogmática penal e à teoria dos direitos fundamentais. Afirma que a prescrição penal, qualquer que seja, extingue a inelegibilidade; que a inelegibilidade é efeito primário da condenação; que, alternativamente, entenda o TSE que o marco inicial é o trânsito em julgado da condenação, e não o da ocorrência da prescrição da pena. PALAVRAS-CHAVE: pena criminal; prescrição; inelegibilidade; direito fundamental de candidatura; máxima efetividade; direito positivo; dogmática eleitoral e penal; overruling. ABSTRACT: The article brings up strong legal critics to the expiry of the statute of limitations on the crime’s effects over the fundamental right of running for public office regarding the legal precedent set on Respe 23.851-TSE, which defined that the term of unelectable condition only begins after the statute of limitations on the crime has expired, demanding overruling. It shows that the “ratio decidendi” of the mentioned decision lacks adequacy to Positive Law, Criminal Dogmatic and to the Fundamental Rights’ Theory. Proclaims that the expiry of the statute of limitation on the crime, whatever kind might it be, extinguishes the unelectable condition; also that the unelectable condition is a primary effect of the criminal sentence; that, alternatively, the Court should consider that the beginning of the unelectable condition term is the final judgment preclusion and not when the statute of limitations on the crime expires. KEYWORDS: criminal sentence; statute of limitations on the crime; unelectable condition; running for public office fundamental right; maximum effectiveness; positive law; electoral and criminal dogmatises; overruling. SUMÁRIO: Introdução; 1 Prescrita a pena criminal, cessa a inelegibilidade diante do direito positivo eleitoral e penal; 2 Inelegibilidade deve ser contada do trânsito em julgado quando houver prescrição da pena; Conclusão; Referências. SUMARY: Introduction; 1 With the expiry of the statute of limitations of the crime the unelectable condition automatically ceases due to positive electoral and criminal law; 2 Beginning of the term of the unelectable condition that must be counted from the date of the expiry of the statute of limitations of the crime; Conclusions; References.